Personality Type of the Main Character Nora Andreana in the Novel The Darkest Embrace Shan A. Fitriani's work: A Psychological Study of Literature - Simamora, Nanci; Lubis, Haris Sutan; Kudadiri, Amhar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research discusses the personality of the main character owned by Nora Andreana in the novel The Darkest Embrace by Shan A. Fitriani using the Hippocrates-Galenus typological theory. This theory states that in the human body there are four personality types, namely: Kholeris, Melancholy, Phlegmatic, and Sanguinis. The four personality types have their own traits or characteristics. This study aims to describe the personality type of the main character Nora Andreana in the novel The Darkest Embrace by Shan A. Fitriani. The research method used is a qualitative description method with data collection techniques using literature study techniques, reading techniques, and notes. The data in this study is in the form of quotes in the novel that show the traits or characteristics of the personality that exist in the main character Nora Andreana in the novel The Darkest Embrace by Shan A. Fitriani. The technical data analysis in this study is to present data, record and observe it, explain the results of the research, and draw conclusions. The result of this study was that 83 data were found on the personality type of the main character Nora Andreana who was more dominant in the Melancholys type which refers to the characteristics of small fighting power, easy to be disappointed, pessimistic, gloomy, anxious, rigid, timid, and thoughtful. This feature is illustrated in Nora Andreana's life which since childhood has not been easy, her life is filled with sadness and tears, because she always loses her loved ones which makes her life even more miserable.